PENGARUH PENGGUNAAN ANALISA TEKNIKAL INDIKATOR STOCHASTIC DAN CANDLESTICK TERHADAP PROFIT TRADER CRYPTOCURRENCY PERIODE 2021 - Mu’thia Wirdah Philazatus Zuhroh; Noor Shodiq Askandar; Afifudin Afifudin (Universitas Islam Malang, 2022)
This study aims to determine the effect of using technical analysis on stochastic and candlestick indicators on cryptocurrency traders' profits during the 2021 period. 170 coins listed on the Indodax exchange which are viewed with daily time frames and their price movement data can be accessed via the charting website tradingview.com are the population in the study. this. As for the research sample, the researchers used a non-probability sampling technique with a purposive sampling method with criteria, namely 5 cryptocurrency coins that have the largest capitalization as of December 2021, cryptocurrency coins that are actively transacted during 2021 which experience bullish and bearish markets, and cryptocurrency coins whose data movement the price can be accessed on the indodax application and the tradingview.com website, from the sample criteria obtained data as much as 1,825 daily price movements. The results of the study prove that the stochastic and candlestick indicators can provide sell signals and buy signals that affect the amount of profit received by cryptocurrency traders during the 2021 period.Keywords: Technical Analysis, Stochastic, Candlestick, Profit, Trader, and Cryptocurrency